STRATEGI MENINGKATKAN KEPUASAN NASABAH TABUNGAN PADA PT. BANK PERKREDITAN RAKYAT HASA MITRA CABANG MAKASSAR - Rosnaini Daga (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of this research is to analyze the strategy used by PT. Bank Perkreditan Rakyat Hasamitra Makassar Branch in increasing customer satisfaction savings. This research was conducted at PT. Hasamitra Bank Perkreditan Branch Makassar on Jl. Dr. Wahidin Sudirohusodo using qualitative descriptive method. The results obtained showed that the strategy used by PT. Hasamitra People's Credit Bank in improving customer satisfaction savings is a standard strategy of bank services. the marketing strategy undertaken has been able to increase the number of customers, this means the marketing strategy undertaken has been effective in increasing the number of customers